MOTIVASI, KEPUASAN, PERSEPSI IMBALAN PERSEPSI SUPERVISI DAN KINERJA DOSEN - Aprilina, Vita (Fakultas Ekonomi Universitas Islam 45, 2017)
The purpose of this study is to determine the effect of work motivation, job satisfaction, perceptions of rewards and perceptions of supervise affect the performance of lecturers in implementing teaching and learning process at Universitas Islam